Stab wound to the right ventricle - Puig, Roberto; Paperán, Juan (Cirugía del Uruguay, 1972)
1) A case of knife wound in the right ventricle oi a young man, treated successfully, is discussed. 2) It reaffirms the concepts found in national bibliography regarding preoperatory preparation and surgical management. 3) The authors point out the need of strict postoperatory of performing direct coronary surgery,